Sustainable and energy efficient hydrogen production via glycerol reforming techniques: A review - Qureshi, F. (Elsevier Ltd, 2022)
Hydrogen-based energy solutions are among the alternative energy choices due to their clean emissions and high efficiency. H2 is a highly convenient energy source, particularly if derived from sustainable feedstock. With the renewed emphasis on biodiesel production globally, large quantities of glycerol are expected to be produced as a major by-product. Reforming of this glycerol can provide a sustainable and H2-rich feedstock. The study reveals that 7H2 molecules were produced/molecule of glycerol in GSR, which is much higher than the commercially available SRM process. This also endorses the concept of circular economy and the 3Rs (Reuse, Reduce, and Recycle) by utilization of a by-product. This review highlights the recent advancements in different types of glycerol reforming technologies for H2 production. The highly endothermic reaction and the coking of Ni-based catalysts are still the main limitations in its commercialization. It has been found that among different glycerol reforming techniques, the GSR is the finest with the least drawbacks. Hence, corresponding solutions to overcome these obstacles are deliberated. Â© 2022 Hydrogen Energy Publications LLC